1988
DOI: 10.1524/ract.1988.4445.1.147
|View full text |Cite
|
Sign up to set email alerts
|

Sorption of Cesium and Strontium on Montmorillonite and Kaolinite

Abstract: Sorption characteristics of Cs+ and Sr++on montmorillonite and kaolinite type clays and soil fractions from various regions of Turkey were studied using the batch method. 137Cs and 90Sr were used as tracers. Concentrations of Cs+ and Sr++ ions ranged from 10-8to 10-2 mol/1; natural groundwater was used and the grain size of the solid particles was < 20 yμm. Equilibrium was reached in 4 - 7 days for Cs+and 7 - 11 days for Sr++. The distribution coefficient, RD, increased with decreasing grain size, suggestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(23 citation statements)
references
References 8 publications
1
22
0
Order By: Relevance
“…This is reflected in the small RIP of the Tro¨dje soils. In kaolinite (1:1 type clay minerals) no specific Cs-binding sites are present (Komarneni, 1978;Erten et al, 1988). Radiocaesium is thus easily extracted from these soils and ageing (radiocaesium diffusion to the 1.0 nm interlayers) will be very small for the Tro¨dje soils.…”
Section: The Cs Soil-to-plant Transfer and Its Predictabilitymentioning
confidence: 99%
“…This is reflected in the small RIP of the Tro¨dje soils. In kaolinite (1:1 type clay minerals) no specific Cs-binding sites are present (Komarneni, 1978;Erten et al, 1988). Radiocaesium is thus easily extracted from these soils and ageing (radiocaesium diffusion to the 1.0 nm interlayers) will be very small for the Tro¨dje soils.…”
Section: The Cs Soil-to-plant Transfer and Its Predictabilitymentioning
confidence: 99%
“…Yu et al [13] observed that the removal of Cs on Na 4 Ti 4 SiO 10 from simulated high level liquid waste (HLLW) is controlled by ion exchange and the best HNO 3 concentration for Cs + removal from HLLW is 1 mol/L. Removal of Cs(I) and Sr(II) on montmorillonite and kalonite studied by Erten et al [14] showed a non linearity of sorption isotherms indicating the involvement of two different adsorption processes. Adsorption of Cs on ammonium molybdophosphate-alumina (AMP-Al 2 O 3 ) was introduced as a new inorganic exchanger following Langmuir and Freundlich isotherms with exothermic nature [15].…”
Section: Introductionmentioning
confidence: 99%
“…Gadde and Laitinen [22] studied the adsorption of lead, cadmium, zinc and thallium ions on hydrated iron, manganese and aluminium oxides with a view to assess the role of oxides in regulating the concentration of these biologically toxic metals in water. Although a good number of papers have been published on Cs uptake [7,8,14,[18][19][20], these in general lack with reference to systematic parametric studies. The present paper is an attempt to proceed/study further the uptake of Cs(I) ions on hydrous manganese and hydrous stannic oxides with special attention to effects of adsorptive concentration, temperature, coions and radiation stability of the adsorbents.…”
Section: Introductionmentioning
confidence: 99%
“…Detailed work examining the sorption/desorption behavior of Cs + and Ba 2+ ions on dierent clays and soil fractions from various regions of Turkey was carried out (Erten et al, 1988;Eylem et al, 1990) In those studies, sorption of Cs + and Ba 2+ cations on magnesite was examined as a function of time, cation concentration and temperature. The interaction of Cs + with various soil fractions is of considerable interest in radioactive waste considerations.…”
Section: Introductionmentioning
confidence: 99%